Przybliżona Metoda Wyznaczania Parametrów Wytrzymałościowych Skał - Zawada, J.; Supeł, S. (Engineering Transactions, 1974)
Experimental results are presented for cylindrical specimens of various diameter -length ratio cut out from four different rocks and tested under uniaxial compression. This method of investigation proposed in Ref. [1] can be used for approximate determination of the strength parameters for brittle materials described by linear fracture criterion. In the present work the theoretical analysis has been performed on the basis of the Coulomb-Mohr fracture criterion. Experimental results have been compared with results obtained by means of the more elaborated triaxial compression technique.